2015
DOI: 10.1021/acsmedchemlett.5b00225
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Selective Janus Kinase 2 Imidazo[4,5-d]pyrrolo[2,3-b]pyridine Inhibitors

Abstract: Early hit to lead work on a pyrrolopyridine chemotype provided access to compounds with biochemical and cellular potency against Janus kinase 2 (JAK2). Structure-based drug design along the extended hinge region of JAK2 led to the identification of an important H-bond interaction with the side chain of Tyr 931, which improved JAK family selectivity. The 4,5-dimethyl thiazole analogue 18 demonstrated high levels of JAK family selectivity and was identified as a promising lead for the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In addition, NPQ-C6 fit better into the JAK2 ATP-binding site. This compound showed a good steric and electronic complementarity with the binding site, being observed the existence of two hydrogen bonds, one of them between the residue Leu 932 and the carbonyl group of the NPQ nucleus, as well as another hydrogen bond between Ser 936 and the carbonyl group of the coumarin moiety which are similar to those observed for known JAK2 inhibitors (Zak et al, 2013; Hart et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…In addition, NPQ-C6 fit better into the JAK2 ATP-binding site. This compound showed a good steric and electronic complementarity with the binding site, being observed the existence of two hydrogen bonds, one of them between the residue Leu 932 and the carbonyl group of the NPQ nucleus, as well as another hydrogen bond between Ser 936 and the carbonyl group of the coumarin moiety which are similar to those observed for known JAK2 inhibitors (Zak et al, 2013; Hart et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…A cross-docking exercise was then carried out to validate the ability of the docking protocol to reproduce the available experimental complexes and to find out the structures endowed with the better propensity to reproduce not only the native binding mode but also the one displayed by other structures ( Figure S1 ). As a result of the cross-docking, we selected the PDB-IDs 4IVD, 20 5CF6, 21 and 6GLA( 22 ) as representatives of JAK1, JAK2, and JAK3 subtypes. In Figure 7 , we report the main interactions established by the native compounds cocrystallized with the structures chosen to represent the three JAK subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Representation of the binding sites of the JAK1, JAK2, and JAK3 structures in complex with the native ligands that were selected for the docking calculations (PDB-ID: 4IVD, 5CF6, and 6GLA, respectively). The conserved residues are represented as sticks with carbon atoms colored in white, while specific amino acids are differently colored (orange, yellow, and green for JAK1, JAK2, and JAK3, respectively). Hydrogen bonds are explicitly reported as black dots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further ADME profiling indicated that 1 was rapidly metabolized across species and was susceptible to generation of reactive metabolites (vide inf ra), which prevented its further progression. Herein we report ADMET and structure-guided optimization of heterocycles at the C-4 position of the imidazopyrrolopyridine core leading to the discovery of a highly selective JAK2 inhibitor, BMS-911543 (11), as a clinical candidate for the treatment of MPNs. Earlier we have reported biological characterization of BMS-911543.…”
mentioning
confidence: 99%